PENGARUH KOMPENSASI FINANSIAL DAN KOMPENSASI NON FINANSIAL TERHADAP KINERJA KARYAWAN PT. ANUGRAH DISTRINDOJAYA SENTOSA - B31111030, RIDUAN TENNAR MANIK (Jurnal Manajemen Update, 2016)
The purpose of this research is to test and analyze whether there is influence of Financial Compensation and Non Financial Compencation the Performance of employees in PT. Anugrah Distrindojaya Sentosa. Types of research used in this study was the design of causal, that is research aimed at analyzed the causal relationship among the variables Financial Compensation, Non Finansial Compensation, and variable Performance. Populasi in this research all employees PT. Anugrah Distrindojaya Sentosa totaling 45 people, with samples used were 40 people. Data from the questionnaires were analyzed by using multiple linear regression analysis. That result prove that the partial among the variables Finansial Compensation and Non Finansial Compensation the Performance of employees are as follows : Partially t value Financial Compensation of 11,042 with significant 0,000 > t table 1,687. It can be concluded variable Financial Compensation partially affect the Performance variables. Partially t value variable Non Financial Compensation of 1,701 with significant 0,097 > t table 1,687. It can be used concluded variable Non Financial Compensation is a variable that has no effect to variable Performance. Keyword : Financial Compensation, Non Financial Compensation, And Employee Performance